Abraham as a covenant mediator - Mitchell, Gordon Barry (Rhodes University, Faculty of Divinity, Department of Divinity, 1978)
Conclusion: The [Abrahamic] stories reveal a man caught up in the struggle of faith. But the God who took the initiative in establishing the Covenant shows that in spite of first appearances, He is faithful. The stories present various pictures of Abraham as a Covenant Mediator. Because he is in a sense Israel in microcosm it is not strange that he is described in the terms of Israel's most important institutions: prophet, priest, and king. Nevertheless the most significant Sitz im Leben is the family. While he is usually meant to be understood as an individual representing his immediate family, his descendants, and even all nations, at times, because he is the founding ancestor of Israel and therefore Israel in microcosm, he is best understood as a "Corporate Person". He and Israel are to be a source of blessing to the nations.
Keywords: Abraham (Biblical patriarch); Covenant theology -- Biblical teaching